On the relationship between interplanetary magnetic field and cosmic ray flux over Antarctica - Selvamurugan, R.; Rao, D.N. (2006)
The total Interplanetary Magnetic Field (IMF) probed by the ACE Satellite during the years 1997-2004 has been used to investigate the corresponding changes observed in the cosmic Ray Flux (CRF) during the same period at Mac Murdo (77.9° S, 166.6° E) in Antarctica. The analysis unambiguously shows that the CRF is predominantly influenced by the total IMF and occasional fluctuations of the CRF perhaps are associated with the Galactic cosmic ray flux changes. However, data on the absolute changes occurring with the Galactic CRF are not known to exist from any independent measurements outside the heliosphere. The data from ULYSSES satellite on high energy alpha particles (Z>=3 and 26-173+ MeV/n) of solar cosmic ray is found to be positively correlated to the CRF flux measured at ground to a large extent. Further, it is to be mentioned that the earthbound phenomena at lower atmosphere like cloud formation, thus, related Climatological effects although seem to have a causal relationship with the CRF need to be more closely examined since the penetration of CRF is found to be significantly depend on the total IMF conditions prevailing just outside our earth at Magnetopause distances.